Nnedi Okorafor magic, myth, morality and the future - Lindow, Sandra J. ca. 20./21. Jh. (Jefferson, North Carolina McFarland & Company, Inc., Publishers, 2023)
"This work is the first book-length scholarly treatment of Nnedi Okorafor's critically acclaimed fiction. Written for an audience that includes serious fans as well as scholars, it is an introduction to Okorafor's work and major influences. The scope of the text is ambitious, featuring detailed analyses of her novels, short story collection, memoir, comics and graphic novel. Particular emphasis is given to Okorafor's most enduring themes, which include healthy young adult development and decision making, the interweaving of fantasy and science fiction, flight as a unifying force and the use of innovative biotechnology in ecological utopian communities. Influences examined include feminism, Afrofuturist and Africanfuturist movements and African mythology. Chapters also detail Okorafor's examinations of colonialism and corporate neocolonialism in Africa and Africa's potential to become a major world power"--
Introduction to Reading Okorafor -- Exploring the Empire of Girls' Moral Development -- Watching Windseekers: Wonder, Anger, Intimacy, Independence and Transformation -- Mythology and Sacrifice in Who Fears Death -- The Book of Phoenix, Motherless Monsters and the Morality of abomination -- Tomorrow Is Now: An Evolution of Young Women's Rights, Trauma, and Resilience -- Magic, Masquerades and Morality -- Degrowth in the Anthropocene Worlds of Le Guin and Okorafor -- Black to Okorafor: Entering the Intersection of Afrofuturism, Comics and the Women's Movement -- Conclusions About Morality, Technology, Magic, and the Lessons of History.
Includes bibliographical references and index
Keywords: Okorafor, Nnedi -- Criticism and interpretation; Science fiction, American -- History and criticism; Science Fiction -- Women authors -- History and criticism; Afrofuturism; African American women authors -- Biography